Capture-recapture analysis of all-cause mortality data in Bohol, Philippines - Sanvictores Diozele; Tallo Veronica; Williams Gail; Carter Karen L; Madera Hazel; Riley Ian (BMC, 2011)
Abstract Background Despite the importance of mortality data for effective planning and monitoring of health services, official reporting systems rarely capture every death. The completeness of death reporting and the subsequent effect on mortality estimates were examined in six municipalities of Bohol province in the Philippines using a system review and capture-recapture analysis. Methods Reports of deaths were collected from records at local civil registration offices, health centers and hospitals, and parish churches. Records were reconciled using a specific set of matching criteria, and both a two-source and a three-source capture-recapture analysis was conducted. For the two-source analysis, civil registry and health data were combined due to dependence between these sources and analyzed against the church data. Results Significant dependence between civil registration and health reporting systems was identified. There were 8,075 unique deaths recorded in the study area between 2002 and 2007. We found 5% to 10% of all deaths were not reported to any source, while government records captured only 77% of all deaths. Life expectancy at birth (averaged for 2002-2007) was estimated at 65.7 years and 73.0 years for males and females, respectively. This was one to two years lower than life expectancy estimated from reconciled reported deaths from all sources, and four to five years lower than life expectancy estimated from civil registration data alone. Reporting patterns varied by age and municipality, with childhood deaths more underreported than adult deaths. Infant mortality was underreported in civil registration data by 62%. Conclusions Deaths are underreported in Bohol, with inconsistent reporting procedures contributing to this situation. Uncorrected mortality measures would subsequently be misleading if used for health planning and evaluation purposes. These findings highlight the importance of ensuring that official mortality estimates from the Philippines are derived from data that have been assessed for underreporting and corrected as necessary.